Address at Memorial Sitting for the Rt Hon Sir Ivor Richardson, PCNZM - Elias, Sian (Victoria University of Wellington Law Review, 2015)
The address was given at No 1 Court, Court of Appeal, Wellington, on Friday 1 May 2015.